2010
DOI: 10.1007/s12630-010-9281-9
|View full text |Cite
|
Sign up to set email alerts
|

Topical lidocaine improves conditions for laryngeal mask airway insertion

Abstract: Purpose We hypothesized that optimal laryngeal mask airway (LMA TM ) insertion conditions might be achieved with topical lidocaine and a smaller dose of propofol. In this study, insertion conditions after topical lidocaine 40 mg followed by propofol 2 mgÁkg -1 were compared with propofol 2 mgÁkg -1 or propofol 3 mgÁkg -1 alone. Methods Ninety patients were recruited for this randomized prospective double-blind study. One group received four sprays of topical lidocaine (40 mg) over the posterior pharyngeal wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…Topical lignocaine decreased the Propofol dose required for induction. Lower incidence of apnea and fewer hemodynamic changes were observed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Topical lignocaine decreased the Propofol dose required for induction. Lower incidence of apnea and fewer hemodynamic changes were observed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous fentanyl is a frequently used opioid for co-induction during LMA insertion ( 28 ). However studies have also shown improved insertion conditions with prior topical pharyngeal lignocaine ( 12 , 13 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laryngospasm was managed with additional propofol 0.5 mg/kg bolus and increased sevoflurane concentration. Laryngospasm was defined as the presence of stridor, or other evidence of upper airway obstruction that subsides with deepening of anesthesia ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference may be due to the use of different age groups, different patient populations, different local practices, and different surgical procedures. Changchien [25] and Bahk [26] have shown that topical anesthesia with lidocaine overtly improves the conditions for laryngeal mask insertion and reduces the dose of anesthetic agents. Indeed, topical anesthesia with lidocaine could reduce the conduction of stimulation from the laryngeal mask airway.…”
Section: Discussionmentioning
confidence: 99%